Nematode-induced interference with vaccination efficacy targets follicular T helper cell induction and is preserved after termination of infection. - Irma Haben; Wiebke Hartmann; Minka Breloer (Public Library of Science (PLoS), 2014)
One-third of the human population is infected with parasitic worms. To avoid being eliminated, these parasites actively dampen the immune response of their hosts. This immune modulation also suppresses immune responses to third-party antigens such as vaccines. Here, we used Litomosoides sigmodontis-infected BALB/c mice to analyse nematode-induced interference with vaccination. Chronic nematode infection led to complete suppression of the humoral response to thymus-dependent vaccination. Thereby the numbers of antigen-specific B cells as well as the serum immunoglobulin (Ig) G titres were reduced. TH2-associated IgG1 and TH1-associated IgG2 responses were both suppressed. Thus, nematode infection did not bias responses towards a TH2 response, but interfered with Ig responses in general. We provide evidence that this suppression indirectly targeted B cells via accessory T cells as number and frequency of vaccine-induced follicular B helper T cells were reduced. Moreover, vaccination using model antigens that stimulate Ig response independently of T helper cells was functional in nematode-infected mice. Using depletion experiments, we show that CD4+Foxp3+ regulatory T cells did not mediate the suppression of Ig response during chronic nematode infection. Suppression was induced by fourth stage larvae, immature adults and mature adults, and increased with the duration of the infection. By contrast, isolated microfilariae increased IgG2a responses to vaccination. This pro-inflammatory effect of microfilariae was overruled by the simultaneous presence of adults. Strikingly, a reduced humoral response was still observed if vaccination was performed more than 16 weeks after termination of L. sigmodontis infection. In summary, our results suggest that vaccination may not only fail in helminth-infected individuals, but also in individuals with a history of previous helminth infections.